Transforming Environments and Rehabilitation / A Guide for Practitioners in Forensic Settings and Criminal Justice - Akerman Geraldine; Bainbridge Claire; Needs Adrian (Routledge - Taylor & Francis Group, 2018)
This is a text that practitioners, commissioners and those involved in forensic services should pay attention to. Acknowledgements, Introduction, Steps to an Ecology of Human Functioning for Forensic Psychology, The Social Context of transition and Rehabilitation, Only Connect: Implications of Social Processes and Contexts for Understanding Trauma, Trauma-Informed Care and Good Lives in confinement: Acknowledging and Offsetting Adverse Impacts of Chronic Trauma and Loss of Liberty, A Campaign for Climate Change: The Role of Therapeutic Relationships within a Climate of Control, The Importance of Personal Safety to Therapeutic Outcome in the Prison Setting, Rehabilitating Offenders: The Enabling Environment of Forensic Therapeutic Communities, Creating a Therapeutic Community from Scratch: Where Do We Start?, Psychologically Informed Planned Environments: A New Optimism for Criminal Justice Provision?, Democratisation and Disability and Defence Mechanisms: Reality Confrontation in Rampton, Relationships and Social Context and Personal Change: The Role of Therapeutic Communities, Wearing Two Hats: Working Therapeutically as a Discipline Prison Officer, The Enabling Environments Award as a Transformative Process, Creating an Enabling Environment in High Security, Establishing Enabling Environment with Young Adult Males in a Custodial Setting, The Heart and Soul of the Transforming Environment: How a Values-Driven Ethos Sustain a Therapeutic Community for Sexual Offenders, The Role of Environmental Factors in Effective Gender-Responsive Programming for Women in the United States: Current Status and Future Directions, Contextual Influences in Prison-Based Psychological Risk Assessment: Problems and Solutions, The Importance of Organisational Factors in Transferring the Principles of Effective Intervention to Offender Rehabilitation in the Real World, Nidotherapy: A Systematic Environmental Therapy, Index.